2022
DOI: 10.1101/2022.05.17.492322
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An automated high-content synaptic phenotyping platform in human neurons and astrocytes reveals a role for BET proteins in synapse assembly

Abstract: Resolving fundamental molecular and functional processes underlying human synaptic development is crucial for understanding normal brain function as well as dysfunction in disease. Based upon increasing evidence of species divergent features of brain cell types, coupled with emerging studies of complex human disease genetics, we developed the first automated and quantitative high-content synaptic phenotyping platform using human neurons and astrocytes. To establish the robustness of our platform, we screened t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 114 publications
(153 reference statements)
0
4
0
Order By: Relevance
“…Finally, astrocytes play critical roles in the establishment of synaptic networks, a key non-cell-autonomous function of astrocytes in the human brain. Previous studies have shown that both rodent and human astrocytes can improve the maturation of hNs (Berryer, 2022;Canals et al, 2018;Hedegaard et al, 2020;Nehme et al, 2018). Using an established glutamatergic hN differentiation protocol (Nehme et al, 2018) combined with an automated synaptic quantification platform (Berryer, 2022), we analyzed synaptic development in hN + hiA cocultures derived from the same parental cell line, as well as hN + hpA co-cultures.…”
Section: Hias Recapitulate Key Functional Features Of Hpasmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, astrocytes play critical roles in the establishment of synaptic networks, a key non-cell-autonomous function of astrocytes in the human brain. Previous studies have shown that both rodent and human astrocytes can improve the maturation of hNs (Berryer, 2022;Canals et al, 2018;Hedegaard et al, 2020;Nehme et al, 2018). Using an established glutamatergic hN differentiation protocol (Nehme et al, 2018) combined with an automated synaptic quantification platform (Berryer, 2022), we analyzed synaptic development in hN + hiA cocultures derived from the same parental cell line, as well as hN + hpA co-cultures.…”
Section: Hias Recapitulate Key Functional Features Of Hpasmentioning
confidence: 99%
“…Human induced neuron (hN) generation, astrocyte co-culture and synapse quantification was performed as previously described (Berryer, 2022;Nehme et al, 2018;Zhang et al, 2013). In brief, hNs with stable integration of iNGN2 in the AAVS1 safe-harbor locus were differentiated on day 0 in N2 medium supplemented with SB431542, XAV939 and LDN-193189 along with doxycycline and Y27632.…”
Section: Hn Generation and Synapse Quantificationmentioning
confidence: 99%
See 2 more Smart Citations